Mortality and cancer incidence among Swedish fishermen with a high dietary intake of persistent organochlorine compounds - Svensson, B-G; Mikoczy, Zoli; Strömberg, Ulf; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'The objective of this study was to determine mortality and cancer incidence in two cohorts of Swedish fishermen with different dietary intakes of persistent organochlorine compounds ' ' METHODS ': 'The following two cohorts of Swedish fishermen were established: a cohort of 2896 subjects from the Swedish east coast (on the Baltic Sea), and a cohort of 8477 subjects from the Swedish west coast. Mortality and cancer incidence were studied in these cohorts and comparisons were made both with the regional populations and between the cohorts ' ' RESULTS ': 'The incidences of stomach and squamous cell skin cancers among the eastcoast fishermen were elevated as compared with those of the regional population [standardized incidence ratio (SIR) 1.6, 95% confidence interval (95% CI) 1.0-2.4 and SIR 2.3, 95% CI 1.5-3.5 respectively] and with the westcoast cohort (IRR 2.2, 95% CI 1.3-3.5 and IRR 1.9, 95% CI 1.2-3.1, respectively), while that of colon cancer was decreased. Moreover, mortality from multiple myelomas was increased among the eastcoast fishermen as compared with that of the general population [standardized mortality ratio (SMR) 3.1, 95% CI 1.2-6.4) and the westcoast fishermen (IRR 3.2, 95% CI 1.2-8.7). A 12% decreased mortality in ischemic heart disease was found for the eastcoast cohort. A slight, but significant increase in such deaths was noted among the westcoast fishermen ' ' CONCLUSION ': 'High consumers of fatty fish, contaminated with organochlorine compounds, had an increased risk for stomach and skin cancer. They also had a suggestive decrease in mortality from ischemic heart diseases.
Keywords: cancer incidence; dietary intake; fish consumption; fisherman; IHD; ischemic heart disease; mortality; multiple myeloma; n-3 polyunsaturated fatty acid; PCP; persistent organochlorine compound; polychlorinated biphenyl; polychlorinated dibenzo-p-dioxin; polychlorinated dibenzofuran; selenium; squamous-cell skin cancer; stomach neoplasms; Sweden